Metabolic Syndrome in Female Patients with Acute Myocardial Infarction (TAJ: Journal of Teachers Association, 2018)
Introduction and objectives: A large proportion of patients with coronary disease have metabolic syndrome. The purpose of this research was to assess the association between the metabolic syndrome (MetS) and acute myocardial infarction in female patients.Methods: This was a case control study. Patients with a first time cardiac event of acute myocardial infarction (AMI) arriving in coronary care unit of Rajshahi Medical College Hospital, Rajshahi, Bangladesh during the period June 2013 to July 2014 were included. Metabolic syndrome and its five components were defined according to criteria set by Adult Treatment Plan III (NCEP ATP III) criteria. Blood sugars, triglycerides, HDL-C were measured within 24hrs of cardiac insult. Hypertension was defined as blood pressure ≥ 130/≥85 mmHg. Abdominal obesity measured by waist circumference which is defined for Asia-Pacific region as ≥ 80 cm for women.Results: Total 103 female patients were evaluated. Mean age was 54.28 ±11.78 and acute myocardial infarction was more in age group 50-59 (34%). More than 60% patients suffering from acute myocardial infarction was age group 40-60 years. The metabolic syndrome was present in 74 (71.8%) female patients with acute myocardial infarction and was more frequent in women than in men (71.8% vs 37.9%, P